Open Lung Approach for the Acute Respiratory Distress Syndrome: A Pilot, Randomized Controlled Trial*. Issue 1 (January 2016) - Kacmarek, Robert M.; Villar, Jesús; Sulemanji, Demet; Montiel, Raquel; Ferrando, Carlos; Blanco, Jesús; Koh, Younsuck; Soler, Juan Alfonso; Martínez, Domingo; Hernández, Marianela; Tucci, Mauro; Borges, Joao Batista; et al.
Abstract : Objective: The open lung approach is a mechanical ventilation strategy involving lung recruitment and a decremental positive end-expiratory pressure trial. We compared the Acute Respiratory Distress Syndrome network protocol using low levels of positive end-expiratory pressure with open lung approach resulting in moderate to high levels of positive end-expiratory pressure for the management of established moderate/severe acute respiratory distress syndrome. Design: A prospective, multicenter, pilot, randomized controlled trial. Setting: A network of 20 multidisciplinary ICUs. Patients: Patients meeting the American-European Consensus Conference definition for acute respiratory distress syndrome were considered for the study. Interventions: At 12-36 hours after acute respiratory distress syndrome onset, patients were assessed under standardized ventilator settings (FIO2 ≥0.5, positive end-expiratory pressure ≥10 cm H2 O). If Pao2 /FIO2 ratio remained less than or equal to 200 mm Hg, patients were randomized to open lung approach or Acute Respiratory Distress Syndrome network protocol. All patients were ventilated with a tidal volume of 4 to 8 ml/kg predicted body weight. Measurements and Main Results: From 1, 874 screened patients with acute respiratory distress syndrome, 200 were randomized: 99 to open lung approach and 101 to Acute Respiratory Distress Syndrome network protocol. Main outcome measures were 60-day and ICU mortalities, and ventilator-free days. Mortality at day-60 (29% open lung approach vs. 33% Acute Respiratory Distress Syndrome Network protocol, p = 0.18, log rank test), ICU mortality (25% open lung approach vs. 30% Acute Respiratory Distress Syndrome network protocol, p = 0.53 Fisher's exact test), and ventilator-free days (8 [0-20] open lung approach vs. 7 [0-20] d Acute Respiratory Distress Syndrome network protocol, p = 0.53 Wilcoxon rank test) were not significantly different. Airway driving pressure (plateau pressure - positive end-expiratory pressure) and PaO2 /FIO2 improved significantly at 24, 48 and 72 hours in patients in open lung approach compared with patients in Acute Respiratory Distress Syndrome network protocol. Barotrauma rate was similar in both groups. Conclusions: In patients with established acute respiratory distress syndrome, open lung approach improved oxygenation and driving pressure, without detrimental effects on mortality, ventilator-free days, or barotrauma. This pilot study supports the need for a large, multicenter trial using recruitment maneuvers and a decremental positive end-expiratory pressure trial in persistent acute respiratory distress syndrome. Abstract : Supplemental Digital Content is available in the text.